Баба Яга: [сказки : для чтения взрослыми детям / художник И. Егорова] - Егорова И. (7 лучших сказок малышам, 2015)
Экземпляры: ф.18 (20181203) / Инвентарный номер: 3011 / Цена: / Сис.шифр: 82.3(2Рос=Рус)-6 / Авт.знак: Б 12 / ГРНТИ: 17.71.91 / ББК: 82.3(2Рос=Рус)-6^VLBC/RL